Respuesta :
Answer:
y = 3
x = 2
Step-by-step explanation:
x+y=5 == -2x - 2y = -10
2x-y = 1 == 2x - y = 1 +
-------------------
-3y = -9
y = 3
x + y = 5
x + 3 = 5
x = 2
(2,3)
Step-by-Step:
(1) x+y=5
2x-y=1
(2) add column by column (positive y plus negative y cancels out, equaling 0)
3x=6
(3) divide both sides be 3
x=2
(4) sub 2 in for x for either equation ( i chose the top one)
2+y=5
(5) subtract 2 from both sides
y=3
(6) put your answer in ordered pairs
(2,3)
Hope this helps
Step-by-Step:
(1) x+y=5
2x-y=1
(2) add column by column (positive y plus negative y cancels out, equaling 0)
3x=6
(3) divide both sides be 3
x=2
(4) sub 2 in for x for either equation ( i chose the top one)
2+y=5
(5) subtract 2 from both sides
y=3
(6) put your answer in ordered pairs
(2,3)
Hope this helps